THE INFLUENCE OF DELTA FERRITE ON THE QUALITY ASSESSMENT OF AUSTENITIC STAINLESS STEEL WELDS FOR THE PRODUCTION OF OVENS - Zdravko Praunseis (Journal of Energy Technology, 2024)
Rust-resistant metals, such as the popular stainless steel, often contain some quantities of delta (δ) ferrite that lower the mechanical properties of welded joints. The results of the study show that theamount of δ-ferrite influences the quality assessment of austenitic stainless steel welds for the pro- duction of ovens using the resistance seam welding process. In this article, the basic device of resistance seam welding for the production of stainless steel welds is described. The device itself will have a significant role in the operation of the line; therefore, it was very precisely constructed and designed.